2023
DOI: 10.3389/fphar.2023.1267924
|View full text |Cite
|
Sign up to set email alerts
|

Association between angiotensin-converting enzyme inhibitor-induced cough and the risk of lung cancer: a Mendelian randomization study

Taikang Yao,
Zhenchao Wu,
Zilu Wang
et al.

Abstract: Background: Observational studies and meta-analyses have demonstrated a positive correlation between the use of angiotensin-converting enzyme inhibitors (ACEIs) and lung cancer. However, the findings remain controversial; furthermore, the relationship between ACEI-induced cough and lung cancer development remains unknown. We used Mendelian randomization (MR) to verify the association between ACEI use, ACEI-induced cough, and the risk of lung cancer.Methods: We performed a two-sample MR analysis to determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…63,64 Clinical studies have validated the correlation between elevated ACE2 expression and a more favorable prognosis in non-small cell lung cancer, 65 consistent with the foundational research discussed earlier. A Mendelian randomization study confirmed an increased risk of lung cancer in individuals prescribed formulations of angiotensin-converting enzyme inhibitors, 66 aligning with the conclusions of a meta-analysis that contradicted the protective role of ACE2 against lung cancer. 67…”
Section: Lung Cancer and Ace2mentioning
confidence: 52%
“…63,64 Clinical studies have validated the correlation between elevated ACE2 expression and a more favorable prognosis in non-small cell lung cancer, 65 consistent with the foundational research discussed earlier. A Mendelian randomization study confirmed an increased risk of lung cancer in individuals prescribed formulations of angiotensin-converting enzyme inhibitors, 66 aligning with the conclusions of a meta-analysis that contradicted the protective role of ACE2 against lung cancer. 67…”
Section: Lung Cancer and Ace2mentioning
confidence: 52%
“…The efficacy of RAS-blockers is often suboptimal in patients with hyperkalemia and severe renal dysfunction. Moreover, these drugs are often associated with adverse effects including dry cough, edema, and fatigue ( Whitlock et al, 2023 ; Yao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin-converting enzyme inhibitors (ACEIs), suppressing the activity of angiotensin-converting enzyme (ACE) that is responsible for the conversion of angiotensin I to angiotensin II, have been the first-line drugs for improving hypertension [ 4 , 5 ]; however, ACEIs have side effects such as an irritating dry cough, angioedema, and abnormal renal function, which seriously affect the quality of life and health of patients [ 6 , 7 , 8 ]. Therefore, developing a new ACEI drug with fewer side effects is urgent for the treatment of hypertension [ 9 ].…”
Section: Introductionmentioning
confidence: 99%